Bone density and anisotropy affect periprosthetic cement and bone stresses after anatomical glenoid replacement: A micro finite element analysis. Issue 9 (14th June 2016) - Chevalier, Yan; Santos, Inês; Müller, Peter E.; Pietschmann, Matthias F.
Abstract: Glenoid loosening is still a main complication for shoulder arthroplasty. We hypothesize that cement and bone stresses potentially leading to fixation failure are related not only to glenohumeral conformity, fixation design or eccentric loading, but also to bone volume fraction, cortical thickness and degree of anisotropy in the glenoid. In this study, periprosthetic bone and cement stresses were computed with micro finite element models of the replaced glenoid depicting realistic bone microstructure. These models were used to quantify potential effects of bone microstructural parameters under loading conditions simulating different levels of glenohumeral conformity and eccentric loading simulating glenohumeral instability. Results show that peak cement stresses were achieved near the cement–bone interface in all loading schemes. Higher stresses within trabecular bone tissue and cement mantle were obtained within specimens of lower bone volume fraction and in regions of low anisotropy, increasing with decreasing glenohumeral conformity and reaching their maxima below the keeled design when the load is shifted superiorly. Our analyses confirm the combined influences of eccentric load shifts with reduced bone volume fraction and anisotropy on increasing periprosthetic stresses. They finally suggest that improving fixation of glenoid replacements must reduce internal cement and bone tissue stresses, in particular in glenoids of low bone density and heterogeneity.